Peranan Kurikulum Dalam Mengatur Menejemen Peserta Didik Di SDN Babakan Raden 02 - Nugroho, Iqbal Adi; Umar, Abubakar; Arifudin, Yadi Fahmi (Peneliti.net, 2023)
This research utilizes a qualitative method and is conducted at SDN Babakan Raden 02. The data collection techniques employed include observation, interviews, and documentary studies. The data analysis techniques consist of data reduction, data presentation, and drawing conclusions. To ensure data validity, the research undergoes scrutiny based on four criteria: credibility, transferability, dependability, utilizing techniques such as prolonged engagement, persistent observation, peer examination, negative case analysis, cross-checking, and triangulation. The research findings suggest that curriculum management in improving educational quality involves implementing a curriculum that meets the needs and achieves the learning objectives, particularly in realizing the educational goals at SDN